Phase Morphology and Mechanical Properties of Aliphatic Waterborne Polyurethane-Ureas: Effect of 1, 6-Hexamethylene Diisocyanate (Hdi)/Isophorone Diisocyanate (Ipdi) Ratio. Issue 3 (March 2015) - Fu, Heqing; Liu, Kang; Yan, Caibin; chen, Weifeng; Wang, Yin
Aliphatic waterborne polyurethane-ureas (WPUU) were prepared using 1, 6-hexamethylene diisocyanate (HDI) and isophorone diisocyanate (IPDI) as mixed diisocyanates. The effects of the HDI/IPDI ratio on the phase morphology of WPUU films including the hydrogen bonding, crystallization of the soft segment and hard segment, and phase separation were investigated. The relationship between the phase morphology and the mechanical properties was also studied. The FTIR spectrum showed that the hydrogen bonding degree in the hard segments increased as the HDI/IPDI ratio increased. XRD analysis revealed the excellent crystallinity of WPUU films. DSC analysis indicated that the degree of phase separation was improved with increasing HDI/IPDI ratio, and DMA analysis showed that the storage modulus of the WPUU film increased at first and then decreased. When the HDI/IPDI ratio was 4:1, the WPUU films exhibited high tensile strength.